Pulmonary function tests of mongoloid and non mongoloid group of Dharan - Ghimire, Nisha; Agrawal, Kopila; Deo, Santosh; Chaudhary, Lok Bandhu; Paudel, Bishnu Hari (Journal of Chitwan Medical College, 2019)
Background: Ethnicity is seen to effect normal reference values and prediction equations of pulmonary function tests (PFTs). The normal reference of PFTs among mongoloid and non mongoloid group of Dharan is not available. The aim of the study was to find out the normal reference values of two groups in Dharan and also to find out the correlation of height, weight and body surface area with different PFT parameters. Methods: This cross-sectional study was conducted among 250 (125 mongoloids and 125 non mongoloids) healthy male subjects. Convenient sampling technique was done. Every 5th patient attendant who was permanent resident of Dharan coming to clinical Physiology lab was selected as subject in each group. Portable PFT machine (CHESTOGRAPH, HI-101 Spirometry system) was used for measurement of our test. The test was conducted according to European Respiratory Society (ERS)/American Thoracic Society (ATS criteria. Results: Independent sample t-test was used to compare means between two groups. There was significantly more height (165.30±8.21 vs 161.43±7.35), p <.05], weight [(59.29±11.64 vs 55.32±10.75), p<.05andbody surface area [(1.64±.172Vs1.57±.149), p<.05], in the non-mongoloid group compared to mongoloid group. PFT parameters were also higher in non-mongoloid group VC [(3.3982±.70725 Vs3.0982±.78832) p<.05], FVC [(3.2798±.74312 Vs 2.988±.81970), p <.05], and FEV1 [(3.0668±.72044 Vs 2.7861±.83061) p<.05]. The prediction equations were also calculated for both groups. Conclusions: There was difference in PFT parameters between two groups. Prediction equations were also different in both groups.